2015
DOI: 10.1016/j.jallcom.2014.12.244
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen on the structural and phase state and the deformation behavior of the ultrafine-grained Zr–1Nb alloy

Abstract: The formation of an ultrafine-grained structure with predominantly high-angle grain boundaries and an average grain size of grain-subgrain structure elements of 0.4 lm in zirconium alloys was shown by electron microscopy and X-ray diffraction analysis. The formation of such structure was found to result in the significant increase of the ultimate and yield strengths in comparison with the initial fine-grained state. The strength characteristics of ultrafine-grained Zr-1Nb-0.22H alloy are higher than the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Bashyam and Zelenay claimed that the alloyed catalysts could regulate electronic structures and enhance catalytic activity . Those alloy catalysts exhibited higher photocatalytic activity than monometallic catalysts, due to their particular properties. For instance, it was indicated that nanoparticles (NPs) of Pt 3 Ni alloy exhibited an extremely high specific activity, about 90 times greater than that of Pt NPs used in conventional catalysts. The reason was that Pt 3 Ni alloy nanocrystals could expose the crystal plane efficiently .…”
Section: Introductionmentioning
confidence: 99%
“…Bashyam and Zelenay claimed that the alloyed catalysts could regulate electronic structures and enhance catalytic activity . Those alloy catalysts exhibited higher photocatalytic activity than monometallic catalysts, due to their particular properties. For instance, it was indicated that nanoparticles (NPs) of Pt 3 Ni alloy exhibited an extremely high specific activity, about 90 times greater than that of Pt NPs used in conventional catalysts. The reason was that Pt 3 Ni alloy nanocrystals could expose the crystal plane efficiently .…”
Section: Introductionmentioning
confidence: 99%
“…Calculated PCIs of H:Nb x Zr 1-x are shown in together with data from literature[64,65,67]. Moreover, two isothermal sections at 600 °C and 788 °C are reported in Figures15 and 16with literature experimental data[12,90].Figure12. Calculated pressure-composition isotherms of H:Nb 2.5 Zr 97.5 (at.…”
mentioning
confidence: 82%
“…The formation enthalpies of the binary hcp-and ε-NbH 2 end-members were fixed to the value obtained by DFT and the entropy of formation was assumed to have the ideal value of -65.4 J mol -1 per hydrogen atom [87]. Interaction parameters in the hydride phases were used and optimized for the HCP_A3, BCC_A2, FCC_C1 and epsilon phases in order to describe as well as possible the calculated mixing enthalpies and all the data from the literature [12,[64][65][66][67]90]…”
Section: Calphad Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the rate of hydrogen absorption by metallic materials is known to be increased with decreasing grain sizes. Therefore, the prospects for the application of the UFG polycrystals as structural materials will largely be determined by the effect of hydrogen on the structural and phase state [5][6][7][8]. While penetrating into material, hydrogen produces a wide range of defects, such as vacancy clusters, and reacts with the existing ones, forming the so-called "defect-hydrogen" systems.…”
Section: Introductionmentioning
confidence: 99%